Applications of Silicone Insulation in Electrical Engineering - Lothongkam, Chaiyaporn (Thailand Electrical Engineering Journal (TEEJ), 2024)
This paper presents a review of the investigation of the properties and production technology of silicone rubber. That is the material of choice for electrical insulation with outstanding specific properties. It deals with the chemical structure, physicochemical, mechanical and electrical properties, dielectric strength, the advantages and use of silicone in medium- and high-voltage system, including the optical properties for partial discharge detection in cable accessories. All of these will be helpful for an electrical engineer.